The Use of Geophysics in the Canadian Radioactive Waste Disposal Program, with Examples from the Chalk River Research Area - Dence, M.; Scott, W. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1979)
Summary A program of integrated geophysical surveys has been developed within the Department of Energy, Mines and Resources in response to requests from Atomic Energy of Canada Ltd. for assistance in verifying the concept of deep underground storage of radioactive waste and in selecting suitable sites for a disposal vault. Both well established and innovative airborne, ground and borehole techniques are being tested for their usefulness in determining overall structure, lithological variations, rock quality, the character of specific fracture systems and long term stability of selected areas. Preliminary results from the Chalk River Nuclear Laboratories property illustrate the use of electrical, seismic and other methods in analysing complex fracture systems.